A generalized upper and lower solutions method for nonlinear second order ordinary differential equations. (1992) - Nieto, Juan J.; Cabada, Alberto
Abstract : The purpose of this paper is to study a nonlinear boundary value problem of second order when the nonlinearity is a Carathéodory function. It is shown that a generalized upper and lower solutions method is valid, and the monotone iterative technique for finding the minimal and maximal solutions is developed.